MANAJEMEN PERUBAHAN DALAM LINGKUP PENDIDIKAN: PENYESUAIAN LEMBAGA PENDIDIKAN ATAS PEMBELAJARAN DARING - Sabrina, Afiifah Nur; Haludin, Guntur; Sabina, Nafiza Kayla; Nursyifa, Putri; Januar, Salsabila Kunti; Tanjung, Syafira Mawada (Bussman Journal : Indonesian Journal of Business and Management, 2024)
Change management in education certainly plays a central role in responding to the dynamics of the rapidly developing digital era. The use of advanced technologies such as AI, machine learning, and digital platforms has revolutionized learning methods, triggering the need for curriculum restructuring, strengthening educators’ digital competencies, and providing adequate infrastructure. Although online learning offers flexibility of time and broad access, challenges such as the digital divide, limited technological literacy, and data privacy issues remain unavoidable issues. To ensure the smoothness of online learning and ensure that online learning runs effectively, an integrated change management approach is needed, including mature strategic planning, measurable implementation, disciplined implementation, and continuous evaluation. Sustainability in the hybrid era requires synergy between online and offline learning methods to maintain a balance between the use of technology and the development of students’ social skills.